PENGARUH INDEPENDENSI, PROFESIONALISME, TINGKAT PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA AUDITOR (Studi Empiris pada Kantor Akuntan Publik (KAP) di Kota Medan) - Lidang A. Veronika Limbong; Nadya Fransiska; Nelli Lumban gaol (Yayasan Akrab Pekanbaru, 2019)
This study aims to examine and provide empirical regarding the effect of the independence, professionalism, level of education and work experience on the performance of the auditor. The research was carried out in Accountant Public Firm in Medan. This study used purposive sampling method. The data were collected through questions survey methods. Analysis data is to use multiple linear regression to look at the coefficient of the determination, the value of F statistics. The results of this study found that the independence, professionalism, level of education and work experience have a positive and significant impact on the performance of auditors. While auditors knowledge to detect errors had a negative effect and significant on the materiality level of judgment in an audit of financial statement. This proves that the higher level of independence, professionalism, level of education and work experience, the higher the performance results generated by the auditor.